(untitled) (Revista Brasileira Multidisciplinar, 2010)
To achieve the goal of preserving environment there are several legal mechanisms, which have already been widely discussed and established. However, environmental degradation continues to grow. So, to improve the preservation of environmental balance, there are new tools that aim to facilitate environmental conservation, returning, with a financial compensation, to those that respect law and provide relevant services to improve environment. In this sense, the present paper shows a brief analysis of the Brazilian Environmental Law with its principles and instruments aimed at the conservation and preservation of environment, proposing to develop and refine the idea of payment for environmental services, also known as the receiver-protector principle, complementing the polluter-pays and user-pays principles. The aim is to discuss this possibility in the current Brazilian law, based on a review of the Brazilian law and of the relevant literature. We concluded that financial benefits may be granted to those who preserve environment as a way of encouraging and improving the National Environmental Policy.